The - Joe Vitale (John Wiley & Sons, Inc., 2008)
Now in an expanded paperback second edition that includes an Attractor Factor IQ test, exercises for putting lessons into practice, new stories, and more, Dr. Joe Vitale presents his even more powerful and effective five-step plan for attracting wealth, happiness, and success to your life